Can poultry gelatin substitute bovine gelatin? : a systematic review and meta-analysis - Moh Taufik; Nurwulan Purnasari; ‪Ilzamha Hadijah Rusdan; Frendy Ahmad Afandi; Mojiono Mojiono; Yoni Atma (AGROINTEK, 2024)
Gelatin is one of the popular ingredients and additives in food industries. They have been applied in various roles, including stabilizers, thickeners, and emulsifiers. Bovine (cattle or cow) is one of the most widely used a source of gelatin. Unfortunately, they are still limited in particular considerations. For example, bovine gelatin is unacceptable in some Hindu communities. And the risks of Bovine Spongiform Encephalopathy (BSE) contamination, spreading, and outbreak related to bovine as a source. To challenge these limitations, poultry is another promising source. Current studies have found a similarity between poultry or chicken-based gelatin and bovine gelatin. However, investigation on the comparability of their gel strength is still rare.  It is generally accepted that gel strength is the most essential characteristic of gelatin.  This systematic review examined the gel strength between poultry gelatin and bovine gelatin. There were 795 papers screened, 29 full-text papers assessed, and 10 papers reviewed. The meta-analysis shows that chicken feet (CFG) and head (CHG) gelatin possessed a higher gel strength value than bovine gelatin. In contrast, the gel strength of chicken skin gelatin (CSG) and bovine gelatin did not differ significantly. The meta-analysis demonstrates that the gel strength of duck feet (DFG) and skin (DSG) gelatin is comparable with bovine gelatin. Thus, this study exposed the feasibility of CSG, DFG, and DSG, which can be the substitute for bovine gelatin.